Gender roles in the African culture : implications for the spread of HIV/AIDS - Ngubane, Siegfried Johan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.